Progress Report on JMDE - Scriven, Michael (Journal of MultiDisciplinary Evaluation, 2006)
We have now put out 5 issues, which is conventionally an occasion for summary and reflection. I’ll keep it brief. We now have 1,750 readers who have asked to be notified of the appearance of each issue: we’ll call them ‘committed readers,’ perhaps our closest approximation to subscribers to hardcopy journals. We have had over 19,000 hits on the website, according to our counter, but do not know how many of these read, or download, or make copies for others, of the material. An independent estimate of the number of hits from Lars Balzar’s website (q.v. via Google) places the numbers a little higher, at 12,000 to 30,000 per day (!). Our issues are now widely announced in a considerable number of journals and websites-and many thanks for their help in dissemination.